Protective Effects of Hydrogen Sulfide Against the ATP-Induced Meningeal Nociception - Koroleva, Kseniia; Ermakova, Elizaveta; Mustafina, Alsu; Giniatullina, Raisa; Giniatullin, Rashid; Sitdikova, Guzel (Frontiers in Cellular Neuroscience, 2020)
We previously showed that extracellular ATP and hydrogen sulfide (H2S), a recently discovered gasotransmitter, are both triggering the nociceptive firing in trigeminal nociceptors implicated in migraine pain. ATP contributes to meningeal nociception by activating P2X3 subunit containing receptors whereas H2S operates mainly via TRP receptors. However, H2S was also proposed as a neuroprotective and anti-nociceptive agent. The aim of this study was to test the effect of H2S on ATP-mediated nociceptive responses in rat meningeal afferents and trigeminal neurons and on ATP-induced degranulation of dural mast cells. Electrophysiological recording of trigeminal nerve activity in meninges was supplemented by patch clamp and calcium imaging studies of isolated trigeminal neurons. The H2S donor NaHS induced a mild activation of afferents and fully suppressed the subsequent ATP-induced firing of meningeal trigeminal nerve fibers. This anti-nociceptive effect of H2S was specific as even stronger effect of capsaicin did not abolish the action of ATP. In isolated trigeminal neurons, NaHS decreased the inward currents and calcium transients evoked by activation of ATP-gated P2X3 receptors. Moreover, NaHS prevented ATP-induced P2X7 receptor mediated degranulation of meningeal mast cells which emerged as triggers of migraine pain. Finally, NaHS decreased the concentration of extracellular ATP in the meningeal preparation. Thus, H2S exerted the multiple protective action against the nociceptive effects of ATP. These data highlight the novel pathways to reduce purinergic mechanisms of migraine with pharmacological donors or by stimulation production of endogenous H2S.